Design and comparison of new fault-tolerant majority gate based on quantum-dot cellular automata *Project supported by the National Natural Science Foundation of China (No. 61271122). (August 2018) - Wang, Xiaoyang; Xie, Guangjun; Deng, Feifei; Quan, Yu; Lü, Hongjun
Abstract: Quantum-dot cellular automata (QCA) is increasingly valued by researchers because of its nanoscale size and very low power consumption. However, in the manufacture of nanoscale devices prone to various forms of defects, which will affect the subsequent circuits design. Therefore, fault-tolerant QCA architectures have become a new research direction. The purpose of this paper is to build a novel fault-tolerant three-input majority gate based on normal cells. Compared with the previous structures, the majority gate shows high fault tolerance under single-cell and double-cell omission defects. In order to examine the functionality of the proposed structure, some physical proofs under single cell missing defects are provided. Besides, two new fault-tolerant decoders are constructed based on the proposed majority gate. In order to fully demonstrate the performance of the proposed decoder, the previous decoders were thoroughly compared in terms of fault tolerance, area and delay. The result shows that the proposed design has a good fault tolerance characteristic, while the performance in other aspects is also quite good.